Real-Time Monitoring of Gas Fields: Prototype at Pt Gamma Energi Pratama Bogor - Firman Adi Nur Fatin; Mukhamad Nurkamid; Rizkysari Meimaharani; Ahmad Bagus Maskula (Department of Informatics, Universitas Islam Negeri Syarif Hidayatullah, 2023)
PT Gamma Energi Pratama is a company engaged in the instrumentation sector. One of the projects undertaken by PT Gamma Energi Pratama is on an oil and natural gas drilling site. The oil drilling process involves a tool called a Gas Jack Compressor originating from the United States. At first, the technician there used the local panel that came with the compressor. But procuring spare parts takes a long time. At the same time, the needs in the field demand to be met immediately. Therefore, the Programmable Logic Controller (PLC) was chosen as a special microcontroller device that can access the compressor via the Modbus Protocol. PLCs can also be connected to Supervisory Control and Data Acquisition (SCADA) applications via Ethernet. This solution monitors data from sensor readings installed on the Gas Jack Compressor. The system is already running with its use only on the local scope. For the development of the system so that monitoring can be carried out in real-time and online, it needs to be linked to flow control devices, database systems, and interfaces for data visualization. Thus, monitoring gas fields can be done in real-time online.